Gas forming pyogenic liver abscess in a diabetic patient: a rare case report - Patro, Shubhransu; Mishra, Surya Narayan; Panda, Sudhansu Sekhar; Mohapatra, Manoranjan (International Journal of Advances in Medicine, 2017)
Pyogenic Liver Abscess (PLA) is an uncommon disease with an annual incidence rate ranging from 2 to 45 cases per 100000 hospital admissions worldwide.Gas-Forming Pyogenic Liver Abscess (GFPLA) is even rarer, which accounts for 7% to 24% of PLA and is associated with a high mortality rate in spite of aggressive management. It is commonly associated with underlying immunosuppression like diabetes mellitus. Gas formation occurs as a result of mixed acid fermentation within the abscess by formic hydrogenlyase, an enzyme produced by certain bacteria. Common presentations include fever and abdominal pain, but can be nonspecific, resulting in a delay of diagnosis. Management includes urgent surgical drainage of the abscess under broad spectrum antibiotic coverage. We report a case of GPLA as a result of Klebsiella species in a case of diabetes mellitus.